Membangun Identitas Brand Melalui Konsistensi Feeds Instagram @Bawapulang.Official - Herwanda, Bilqis Agneza; Restu Ismoyo Aji (Journal of Creative Student Research, 2023)
A brand is said to succeed when a brand name is at the top of mind level, meaning that without explicitly mentioning the brand name, consumers can spontaneously know what the brand is. To achieve this, of course, there has been a lot of process going through to build strong identities. High-rise brand names are certainly accompanied by good delivery, such as a catchy logo, striking colors, anti-mainstream fonts, eye-catching supergraphs, or large promotions. Various forms of branding were carried out to get the spotlight, the Bawangulang application through its social media page @bawapulang.official. The purpose of this study is to find out how @bawap home.official consistently builds its brand through social media uploads that have unique and striking design styles. This study used the blabla method. Research results show that consistency branding has an effect on their awareness.